The Readmission Agreement of Turkey - Çınar, Evrim (Border Crossing, 2018)
The irregular migration flows in the last decade from countries, where there are social unrest, civil wars and economic turmoil, towards developed western countries are one of the most populated human movements since the WWII. Hence each immigration flow has its own characteristics, the current irregular flows reveal a new migration outcome; the balance between State Security and Migrant Security. Since the migration policies are control based in some destination countries, they take precaution in order to reduce the irregular immigration flows by signing bilateral readmission agreements with 3rd countries. In that respect, Turkey and European Union relations in terms of irregular migration flows play a crucial and critical role due to its condition of transit migration state. The European Union accession process brought Turkey heavy duties. Controlling and preventing irregular migration became an obligation to its membership and to achieve its goals Turkey signed a readmission agreement with European Union. However, as any method of preventing irregular migration flows, Readmission Agreement of Turkey effect the balance between destination country security and irregular migrant security, especially refugees and asylum seekers rights. The main goal of this article is to find an answer to this question: does the Readmission Agreement of Turkey provide a balance between State Security and Migrant Security? This article intends to analyze the adverse security conditions of irregular migrants and state security compulsions.